Oxytocin promotes prosocial behavior and related neural responses in infant macaques at-risk for compromised social development. (April 2021) - Festante, Fabrizia; Rayson, Holly; Paukner, Annika; Kaburu, Stefano S.K.; Toschi, Giulia; Fox, Nathan A.; Ferrari, Pier Francesco
Abstract: Although positive effects of oxytocin (OT) on social functioning are well-demonstrated, little is known about the mechanisms through which OT may drive early social development, or its therapeutic efficacy in infancy. To address these critical issues, we investigated the effects of exogenous OT on neural (EEG) and behavioral responses during observation of live facial gestures in infant macaques with limited social exposure (i.e. nursery-reared). Three key findings were revealed. First, OT increased alpha suppression over posterior scalp regions during observation of facial gestures but not non-biological movement, suggesting that OT targets self-other matching and attentional cortical networks involved in social perception from very early infancy. Second, OT increased infant production of matching facial gestures and attention towards the most socially-relevant facial stimuli, both behaviors typically silenced by early social deprivation. Third, infants with higher cortisol levels appeared to benefit the most from OT, displaying greater improvements in prosocial behaviors after OT administration. Altogether, these findings suggest that OT promotes prosocial behaviors and associated neural responses likely impacted by early social adversity, and demonstrate the potential of OT administration to ameliorate social difficulties in the context of neurodevelopmental and early-emerging psychiatric disorders, at a developmental stage when brain plasticity is greatest.